Cardio-respiratory health effects of exposure to traffic-related air pollutants while exercising outdoors: A systematic review - Madureira, Joana (2020)
Despite physical exercise provides numerous health benefits, outdoor exercisers are frequently exposed to traffic-related air pollutants (TRAP) known to be associated with respiratory and cardiovascular diseases. The aim of this systematic review was to investigate the effects of TRAP exposure, specifically particulate matter and nitrogen dioxide (NO2), during outdoor exercise on cardio-respiratory health effects. Systematic database searches of PubMed, Web of Science, Scopus and Medline were performed by two researchers to identify peer-reviewed studies from 2000 to 2018. Combinations of keywords related to cardio-respiratory health effects, physical exercise and ambient air pollution were used. Thirteen studies were included, originating predominantly from European countries but also the American. They suggested that exercising in an environment with high TRAP exposure increases markers of respiratory and systemic inflammation, as well as, impairs the vascular function and increases artery pressure, when compared with an environment with low-TRAP exposure. In addition, the smaller particles appear to have the most severe health consequences compared with the larger coarse particles and NO2. This study also provides evidence that specific groups of the population have enhanced susceptibility to adverse effects from particulate matter exposure while exercising. There is a need for more studies focused on the relationship between air pollution, physical exercise and health, as large societal benefits can be obtained from healthy environments that can promote outdoor physical exercise.